2007
DOI: 10.1093/humrep/dem118
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin in relation to insulin resistance and markers of hyperandrogenism in lean and obese women with polycystic ovary syndrome

Abstract: Visfatin is associated with insulin resistance and markers of hyperandrogenism in lean PCOS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
97
3
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 23 publications
16
97
3
6
Order By: Relevance
“…Only lipocalin-2 levels-to-waist circumference ratio was higher in postmenopausal PCOS than in control women, stressing the role of visceral adipose tissue. Of note, in this study, visfatin levels correlated positively with FAI in postmenopausal PCOS women similar to correlations found in PCOS women of reproductive age (42).…”
Section: Discussionsupporting
confidence: 88%
“…Only lipocalin-2 levels-to-waist circumference ratio was higher in postmenopausal PCOS than in control women, stressing the role of visceral adipose tissue. Of note, in this study, visfatin levels correlated positively with FAI in postmenopausal PCOS women similar to correlations found in PCOS women of reproductive age (42).…”
Section: Discussionsupporting
confidence: 88%
“…It has previously been reported that the gene expression and circulating levels of visfatin were increased in women with PCOS compared with age-and BMImatched controls (Tan et al 2006a, Chan et al 2007, Kowalska et al 2007, Panidis et al 2008, Carmina et al 2009, Ozkaya et al 2010, Plati et al 2010, Seow et al 2011, as shown in Table 1. However, several recently published studies did not find a difference in plasma or serum visfatin levels between patients with PCOS and control groups (Guducu et al 2012, Lajunen et al 2012, Olszanecka-Glinianowicz et al 2012.…”
Section: Visfatinmentioning
confidence: 86%
“…Patients with PCOS may present a variety of reproductive and metabolic disturbances, including oligo/ anovulation, polycystic ovary in the ultrasound, and hyperandrogenism, as well as insulin resistance [2]. Moreover, it has been shown that beta cell dysfunction is present in PCOS individuals [3].…”
Section: Introductionmentioning
confidence: 99%